An Oral Contraceptive Containing Estetrol 15 MG and Drospirenone 3 MG Has Limited Effects on Endocrine and Metabolic Parameters - Klipping, Christine (J Endocr Soc, 2021)
Background: Most combined oral contraceptives (COCs) contain ethinylestradiol (EE), an estrogen component known to increase the risk of venous thromboembolic events. Previous phase 2 trials have shown that Estetrol (E4), a naturally-occurring estrogen produced by the human fetal liver, in combination with Drospirenone (DRSP), inhibits ovulation and is associated with favorable vaginal bleeding, safety and tolerability profiles and high user satisfaction. When administered in doses up to 10 mg for less than 3 months, E4 either alone or in combination with DRSP showed limited effects on liver function as well as on metabolic and endocrine parameters. However, the impact of E4 15 mg/DRSP 3 mg, the selected dose for pregnancy prevention (hereafter referred to as E4/DRSP), on metabolic and endocrine parameters was never investigated. Methods: A randomized, open-label, controlled, three-arm parallel study was conducted in 101 healthy volunteers aged 18-50 years with a body mass index between 18.0 and 30.0 kg/m(2). Of the randomized individuals, 98 subjects received either E4/DRSP (n=38), EE 30 µg/levonorgestrel (LNG) 150 µg (n=29) or EE 20 µg/DRSP 3 mg (n=31) COCs for six consecutive treatment cycles of 28 days. Endocrine and metabolic parameters were measured at baseline, cycle 3 and cycle 6. Results: FSH and LH decreased with both EE/LNG (-84% and -92%, respectively) and EE/DRSP (-64% and -90%, respectively), whereas E4/DRSP slightly increased FSH (31%) and had minor effect on LH (-8%). Total cortisol increased by more than 100% during treatment with EE/LNG (109%) and EE/DRSP (107%), while E4/DRSP only slightly increased total cortisol (26%). The effects of E4/DRSP, EE/LNG and EE/DRSP on other endocrine parameters including androstenedione (-31%, -49% and -40%) and free testosterone (-50%, -50% and -71%) were similar. Liver proteins, except CRP, increased from baseline in all treatment groups. The increase in angiotensinogen, CBG, and TBG levels was significantly lower for E4/DRSP (75%, 40% and 17%) in comparison with EE/LNG (170%, 152% and 37%) and EE/DRSP (207%, 140% and 70%). SHBG substantially increased for EE/DRSP (251%), while EE/LNG and E4/DRSP had limited effects on SHBG (74% and 55%, respectively). Triglycerides changed to a lesser extent for E4/DRSP (24%) compared to EE/DRSP (66%); EE/LNG increased triglycerides levels by 28%. Moreover, E4/DRSP had minimal impact on lipid parameters including HDL (4%), Apolipoprotein A1 (5%) and Apolipoprotein B (4%) compared to baseline, and no effects on carbohydrate metabolism. Conclusion: These data confirm that E4/DRSP has limited effects on liver proteins, lipid and carbohydrate metabolism, cortisol, and gonadotropins. The effect on other endocrine parameters, including suppression of ovarian steroids, was typical for a COC. In conclusion, combining E4 15 mg with DRSP 3 mg resulted in a different and potentially favorable metabolic profile.